Current landscape of climate change adaptation and health preparedness among indigenous populations in Southeast Asia - Sheena Ramazanu; Lowilius Wiyono; Hammoda Abu‐Odah; Rey G. Comabig; Shuaibu Saidu Musa; Jemilah Mahmood; Yong Zhin Goh; Nurul Amanina Binte Hussain; Siddharthen Rajasegaran; Thakshayeni Skanthakumar; Adriana Viola Miranda (Public Health Challenges, 2023)
Abstract Human‐induced climate change poses a pervasive threat to the world. Human activities, such as deforestation, farming livestock, and burning fossil fuels, are key drivers of climate change. Like other regions, the Southeast Asian region is greatly impacted by climate change. The article focuses on examining the current landscape of climate change adaptation and health preparedness among indigenous populations in Southeast Asia (SEA). Climate change will affect the indigenous populations disproportionately. Over the years, indigenous people living in SEA have faced increasing challenges. For instance, air pollution resulting from forest fires causes respiratory conditions, skin irritations, and other significant health risks. The article also highlights climate change–related health system preparedness in ASEAN and indigenous strategies in navigating climate change adaption. As the saying goes, “actions speak louder than words.” To develop sustainable regional climate change adaptation strategies, representation and voices of indigenous peoples matter. At ASEAN level, although the ASEAN Working Group on Climate Change was convened to develop policies and coordinate action plans among its member states, it is now key to include and learn from the instrumental strategies of indigenous communities in conserving, protecting, and restoring forests. Beyond acknowledging the efforts of indigenous communities on paper, it is now time to translate scientific knowledge into practical actions. It is necessary for us to value and recognize indigenous peoples, particularly in SEA as valued agents in co‐creating sustainable solutions for climate agenda. Centering indigenous peoples’ knowledge in climate adaptation is crucial for strengthening collective resilience in climate action strategies. Conclusively, the article advocates for the prioritization of indigenous communities’ leadership efforts in ASEAN‐wide climate action initiatives and climate action policy.